2022
DOI: 10.48550/arxiv.2202.04336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Searching for extra Higgs bosons via $pp\to H,A\to τμ, ττ$ at the Large Hadron Collider

Abstract: We follow the heavy Higgs searches at the Large Hadron Collider (LHC) for H → τ µ by CMS, and H → τ τ by ATLAS and CMS, to study the prospects of discovering the extra Higgs states in pp → H, A → τ µ, τ τ with eµ + / E T and j τ µ + / E T final states, where j τ = π , ρ , a 1 and / E T is missing transverse energy. In a general two Higgs doublet model framework without Z 2 symmetry, extra Yukawa couplings ρ τ τ and ρ τ µ can drive H, A → τ τ and τ µ channels at hadron colliders, following gluon-gluon fusion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Gori et al 57 showed in the context of a flavorful model that the dominant decay mode of a heavy scalar can be into a top and a charm and they discuss production and detection of this mode at the LHC. They also point out that the dominant decay mode of the charged Higgs, even about the top threshold, can be into charm plus bottom; a study of this process at linear colliders was recently carried out by Hou et al 58 In addition, Hou et al 27,59 studied flavor changing leptonic decays of heavy Higgs bosons at the LHC and future proton-proton colliders. In fact, CMS has been searching 60 for lepton flavor violating decays of heavy Higgs bosons in Run II.…”
Section: Heavy Higgs Decaysmentioning
confidence: 99%
“…Gori et al 57 showed in the context of a flavorful model that the dominant decay mode of a heavy scalar can be into a top and a charm and they discuss production and detection of this mode at the LHC. They also point out that the dominant decay mode of the charged Higgs, even about the top threshold, can be into charm plus bottom; a study of this process at linear colliders was recently carried out by Hou et al 58 In addition, Hou et al 27,59 studied flavor changing leptonic decays of heavy Higgs bosons at the LHC and future proton-proton colliders. In fact, CMS has been searching 60 for lepton flavor violating decays of heavy Higgs bosons in Run II.…”
Section: Heavy Higgs Decaysmentioning
confidence: 99%
“…The region shaded in red corresponds to the exclusion limit from searches by the ATLAS [28] collaboration for a heavy scalar decaying into a two tau leptons with integrated luminosity of 139 fb −1 (see also ref. [30]). We fix the trilinear coupling to λ eff = 0.1 which affects only the process involving H.…”
Section: Production At the Lhcmentioning
confidence: 99%